Identification and characterization of UDP-glucose:Phloretin 4′-O-glycosyltransferase from Malus x domestica Borkh. (October 2016) - Yahyaa, Mosaab; Davidovich-Rikanati, Rachel; Eyal, Yoram; Sheachter, Alona; Marzouk, Sally; Lewinsohn, Efraim; Ibdah, Mwafaq
Abstract: Apples ( Malus x domestica Brokh.) are among the world's most important food crops with nutritive and medicinal importance. Many of the health beneficial properties of apple fruit are suggested to be due to (poly)phenolic metabolites, including various dihydrochalcones. Although many of the genes and enzymes involved in polyphenol biosynthesis are known in many plant species, the specific reactions that lead to the biosynthesis of the sweet tasting dihydrochalcones, such as trilobatin, are unknown. To identify candidate genes for involvement in the glycosylation of dihydrochalcones, existing genome databases of the Rosaceae were screened for apple genes with significant sequence similarity to Bacillus subtilis phloretin glycosyltransferase. Herein reported is the identification and functional characterization of a Malus x domestica gene encoding phloretin-4′- O -glycosyltransferase designated Md Ph-4′-OGT. Recombinant Md Ph-4′-OGT protein glycosylates phloretin in the presence of UDP-glucose into trilobatin in vitro . Its apparent K m values for phloretin and UDP-glucose were 26.1 μM and 1.2 mM, respectively. Expression analysis of the MdPh-4′-OGT gene indicated that its transcript levels showed significant variation in apple tissues of different developmental stages. Graphical abstract: Highlights: A phloretin-4′- O -glycosyltransferase was identified from apple. The recombinant glycosyltransferase glycosylates phloretin in the presence of UDP-glucose into trilobatin. Expression analysis suggests that the enzyme may play a crucial role in trilobatin biosynthesis.